A study for validating, rectifying and optimizing the flow in the test section of a circulating water channel - Varghese, Kiran George; Nair, Vinay Gopi; Godey, Avinash; Kumar, P. G. Sunil (Journal of Naval Architecture and Marine Engineering, 2021)
The Circulation Water Channel (CWC) is an experimental facility available at Indian Maritime University, Visakhapatnam Campus. A study for comparing the flow pattern and velocity in the test section, for different configurations of the CWC, is complex. To study the flow, a physical model of the CWC, with different configurations, should be made, which in overall is a complicated and time-consuming exercise. But this difficulty can be overcome through using Computational Fluid Dynamics (CFD) analysis, as in this study, where a CFD analysis is done using ‘STAR-CCM+’ software. A CFD model of the existing CWC [corresponding to the 1:4 scale setup at IMUV], is first made, and its validity is checked, by comparing the results of the CFD analysis, against those results obtained from the experimental analysis. On successfully validating the results, modifications are suggested for rectifying the disturbance which is present in the test section. The test section is the area in the CWC where experimental activities are carried out. In order to carry out the experiments with a certain degree of accuracy, it is important to have a smooth streamlined flow in the test section. To ensure this, a honeycomb structure is positioned such that the flow enters the test section through the honeycomb, which streamlines the flow. On successfully rectifying the disturbance, studies are carried out to improve the streamlined flow in the test section, for which, different configurations of honeycomb structure are studied. The optimum honeycomb structure, which produces a smooth flow in the test section of a CWC is found out, by conducting analyses for different shapes - i.e. for shapes ranging from rectangular to hexagonal and circular, against different inlet velocities. The present paper sums up the findings of our earlier research, ‘CFD as a Tool to Validate and Modify the Flow in the Test Section of a Circulating Water Channel’, and ‘Study of Flow in the Test Section of a Circulating Water Channel by Varying the Honey Comb Cross Section’, which were published in the conference proceedings of Indian Institute of Technology, Madras, and Indian Maritime University, Visakhapatnam, respectively.